Revision of the bark louse genus Bicuspidatus (Psocodea: Peripsocidae) with description of a new species from China - Cao, Leran; Liu, Xingyue (Zootaxa, 2024)
Bicuspidatus is a small genus of the family Peripsocidae, erected by Li (1993) with B. pulchipunctatus as the type species. Adults of this genus can be easily distinguished from other peripsocids by the phallosome with bicuspid apical process in males or by the subgenital plate with modestly elongated, distally bilobed posterior lobe in females. Bicuspidatus currently comprises three species: B. guangdongensis Li, 1993, B. pulchipunctatus Li, 1993 and B. sigillatus Li, 1993, all are known only from Guangdong Province, China. According to previous studies, these three species can be distinguished by the markings on the forewings and a few characteristics of phallosome (Li 1993, 2002). In this study, we present a taxonomic revision of Bicuspidatus based on examination of 40 specimens collected from various localities, including the type specimens of B. guangdongensis, B. pulchipunctatus and B. sigillatus. Furthermore, 12 of them were used for molecular analyses based on partial sequences of COI gene. As a result, B. guangdongensis and B. sigillatus are here considered as junior synonyms of B. pulchipunctatus. We redescribe B. pulchipunctatus and describe a new species from Xizang Autonomous Region, China. An updated distribution map and a revised key to the species of Bicuspidatus are also provided.